2023
DOI: 10.3389/fpls.2023.1143813
|View full text |Cite
|
Sign up to set email alerts
|

Knockout of elF4E using CRISPR/Cas9 for large-scale production of resistant cucumber cultivar against WMV, ZYMV, and PRSV

Abstract: CRISPR/Cas9 is one of the most robust technologies for plant breeding enabling precise and efficient modifications in a genome. This technology is being used for the manipulation of target genes in a host to develop resistance against the plant pathogens. Cucumis sativus elF4E is one of the target genes playing a key role in viral infection during interaction with potyvirus viral proteins genome linked (VPg). Nevertheless, the allelic and positional effect of elF4E mutations in C. sativus is to be clarified in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…eIF4E is a hotspot for conferring crop resistance against potyviruses. For example, genetic knockout or deletion of eIF4E using CRISPR/Cas9 technology confers resistance to cucumber vein yellowing virus, ZYMV, WMV and PRSV‐W in cucumber (Chandrasekaran et al., 2016 ; Fidan et al., 2023 ). Another study reported that knockout of eIF4E using CRISPR/Cas9 in melon confers resistance to Moroccan watermelon mosaic virus (Pechar et al., 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…eIF4E is a hotspot for conferring crop resistance against potyviruses. For example, genetic knockout or deletion of eIF4E using CRISPR/Cas9 technology confers resistance to cucumber vein yellowing virus, ZYMV, WMV and PRSV‐W in cucumber (Chandrasekaran et al., 2016 ; Fidan et al., 2023 ). Another study reported that knockout of eIF4E using CRISPR/Cas9 in melon confers resistance to Moroccan watermelon mosaic virus (Pechar et al., 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…A mutation in the gene encoding the cap-binding protein eIF4E induced resistance to the Moroccan watermelon mosaic virus in melon [133,138]. CRISPR/Cas9 mutations in eIF4E were successfully applied for breeding cucumber plants resistant to zucchini yellow mosaic virus, watermelon mosaic virus and papaya ringspot virus (Table 2) [117]. Through the induction of mutations in the gene CmRDR1c1/c2 encoding RNA-dependent RNA polymerase 1b, it has been possible to gain a deeper understanding of the mechanisms of diversified resistance in melon against viruses from various families [161].…”
Section: Enhancing Resistance To Biotic Stresses Through Genome Editingmentioning
confidence: 99%
“…In conclusion, there is an increasing emerging literature on CRISPR/Cas9 published over the last years utilizing agrobacterium mediated transformation in cucurbits to confer resistance against pathogens despite the low efficiencies of the method Fidan et al, 2023;. In our opinion, optimization of this method could lead to similar results in our hands.…”
Section: Agrobacterium Mediated Transformation Is Limiting High-throu...mentioning
confidence: 64%